2014
DOI: 10.5489/cuaj.2108
|View full text |Cite
|
Sign up to set email alerts
|

Stemming the tide of mild to moderate post-prostatectomy incontinence: A retrospective comparison of transobturator male slings and the artificial urinary sphincter

Abstract: Introduction: The AUS remains the gold standard treatment for post-prostatectomy incontinence (PPI), although most patients with mild-moderate PPI prefer a sling without strong evidence of procedural equivalence. This study compares outcomes of 2 procedures for the treatment of mild-moderate PPI. Methods: A retrospective review of 124 patients (76 transobturator sling, 48 AUS) with mild-moderate PPI requiring intervention over an 8-year period. The primary outcome was continence. Secondary outcomes included gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…[39] study, no significant difference in the overall complication rate was observed between the two study groups. However, severe complications (Clavien–Dindo Grade IIIb) occurred only in the AUS group, in agreement with the Hoy and Rourke study [38].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…[39] study, no significant difference in the overall complication rate was observed between the two study groups. However, severe complications (Clavien–Dindo Grade IIIb) occurred only in the AUS group, in agreement with the Hoy and Rourke study [38].…”
Section: Discussionsupporting
confidence: 90%
“…Only two previous studies compared AUS with a fixed sling [38,39]. Hoy and Rourke [38] performed a retrospective study of 124 patients (76 AdVance, 48 AUS) with mild‐to‐moderate PPI and no significant differences were detected between treatments for continence outcomes and complications. The inclusion of mild UI, longer follow‐up and higher proportion of patients with worse features in the AUS group may explain the disagreement with our present results.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of PPI being approximately 8.4% [2], nearly 5% of the patients after radical prostatectomy even undertake surgical therapy for urinary incontinence within the first 15 years of treatment [3], highlighting the high patient demand in this field. The artificial urinary sphincter (AUS) is an established surgical treatment option for the treatment of PPI [4]; nevertheless, the usage of male slings could in the future supersede its use as the gold standard for certain indications [5].…”
Section: Introductionmentioning
confidence: 99%
“…While the Advance sling has shown effectiveness in treating mild to moderate post-prostatectomy incontinence. 3 This current work builds on the concept of further delineating which patient should or should not be offered a male sling. The most important association our study adds to the literature is that for those otherwise well selected patients preoperative pad usage is the most important predictor of sling success.…”
Section: Zemp Et Al Factors Associated With Failure Of Non-adjustable Male Trans-obturator Slingsmentioning
confidence: 99%
“…Many consider the artificial urinary sphincter the gold standard of treatment for PPI but in mild to moderate cases of incontinence, slings may offer similar efficacy. 3 Additionally, when given a choice, 92% of men prefer a male sling over an AUS to avoid the use of a mechanical device and associated manipulation of a scrotal pump. 4 In 2006, the AdVance TM transobturator male sling was introduced as a minimally invasive alternative to the AUS (AMS, Minnetonka, MN).…”
Section: Introductionmentioning
confidence: 99%